Rising temperature modulates pH niches of fen species - Hájek, Michal; Těšitel, Jakub; Tahvanainen, Teemu; Peterka, Tomáš; Jiménez‐Alfaro, Borja; Jansen, Florian; Pérez‐Haase, Aaron; Garbolino, Emmanuel; Carbognani, Michele; Kolari, Tiina H. M.; Hájková, Petra; Jandt, Ute; et al. (Global change biology, 2022)
Rising temperatures may endanger fragile ecosystems because their character and key species show different habitat affinities under different climates. This assumption has only been tested in limited geographical scales. In fens, one of the most endangered ecosystems in Europe, broader pH niches have been reported from cold areas and are expected for colder past periods. We used the largest European‐scale vegetation database from fens to test the hypothesis that pH interacts with macroclimate temperature in forming realized niches of fen moss and vascular plant species. We calibrated the data set (29,885 plots after heterogeneity‐constrained resampling) with temperature, using two macroclimate variables, and with the adjusted pH, a variable combining pH and calcium richness. We modelled temperature, pH and water level niches for one hundred species best characterizing European fens using generalized additive models and tested the interaction between pH and temperature. Fifty‐five fen species showed a statistically significant interaction between pH and temperature (adj p ˂ .01). Forty‐six of them (84%) showed a positive interaction manifested by a shift or restriction of their niche to higher pH in warmer locations. Nine vascular plants and no moss showed the opposite interaction. Mosses showed significantly greater interaction. We conclude that climate significantly modulates edaphic niches of fen plants, especially bryophytes. This result explains previously reported regional changes in realized pH niches, a current habitat‐dependent decline of endangered taxa, and distribution changes in the past. A warmer climate makes growing seasons longer and warmer, increases productivity, and may lower the water level. These effects prolong the duration and intensity of interspecific competition, support highly competitive Sphagnum mosses, and, as such, force niches of specialized fen species towards narrower high‐pH ranges. Recent anthropogenic landscape changes pose a severe threat to many fen species and call for mitigation measures to lower competition pressure in their refugia. Analysis of extensive European fen vegetation data revealed that pH niches of more than half of specialist plant species are significantly modulated by macroclimate temperature. In most cases, pH niches are shifted towards a higher pH range in warmer locations, likely caused by increasing competition from superior species in a warm climate. Therefore, climate change poses a threat to many specialist fen species, forcing them towards narrower high‐pH ranges where restoration measures to lower competition pressure are urgently needed.